Correlation of patient reported outcomes among patients with chronic low back pain and controls - Spencer A. Baker; Kelsey A. Clark; Andrew K. Gibbons; Ammon Gallart; Anton E. Bowden; Ulrike H. Mitchell; David T. Fullwood (BMC Musculoskeletal Disorders, 2025)
Abstract Background Chronic low back pain (CLBP) is a prevalent condition with significant physiological, psychological, social, and economic impacts. A range of patient-reported outcomes (PROs) are used to collect self-reported perceptions of patient health and well-being relating to the condition. Correlations between different types of PROs have previously been demonstrated – for example, between PROs that measure pain, and those that measure anxiety. Furthermore, PROs have evolved over time, and there exist strong correlations between more recently developed outcomes, such as PROMIS PROs, and legacy PROs. However, most studies in this area focus only on subjects with CLBP. It would be enlightening to determine whether the same correlations between PROS exist in healthy subjects, and whether and how the presence of CLBP moderates the relationships between these PROs. This comparative cross-sectional study hypothesizes that: • PRO metrics correlate with CLBP occurrence. • Legacy and PROMIS PROs are correlated in CLBP contexts. • CLBP moderates the relationships between PROs. • Latent factors may identify characteristics that most influence variance in outcomes. Methods We compared outcomes of legacy PROs with PROMIS PROs collected from participants aged 35–65 with (n = 133) and without (n = 100) CLBP. Welch t-tests compared PRO scores between groups. Linear regressions evaluated the relationship between legacy and PROMIS PROs, accounting for CLBP as a binary variable. An exploratory factor analysis identified latent factors summarizing variance in the PROs. Results Cases reported significantly lower scores than controls across all PROs except for activity level. Strong correlations emerged between several PROMIS metrics and two legacy PROs measuring pain intensity and disability. CLBP significantly moderated these relationships. Moderate correlations were noted between PROMIS metrics and pain catastrophizing and anxiety, with weaker correlations for activity level. Five latent factors were identified, capturing key characteristics that influence variance. Conclusions Legacy and PROMIS PROs performed similarly in terms of correlation with CLBP, suggesting they capture overlapping information. However, latent factor analysis indicates potential for designing more focused PROs, targeting characteristics in these factors, to better capture variance in outcomes across individuals with and without CLBP. Clinical trial number Not applicable.